Music of the heart - Craven, Wes.; Streep, Meryl; Quinn, Aidan; Estefan, Gloria; Bassett, Angela; Miramax Films; Craven/Maddalena Films (Studio City, Calif. Craven-Maddalena Films, 2000)
The true story of a young teacher who fights against the board of education in her bid to teach underprivileged kids in a Harlem school the beauty of music through the violin. In her struggle she loses everything as the system comes down on her with all their might but her determination for the kids happiness helps her to battle back with wonderfully inspirational results.
"Inspired by the documentary Small wonders, based on the life story of Roberta Guaspari."
Originally released as a motion picture.
Distributed in the Philippines by Viva Video.
Summary from the cover.
Director of photography, Peter Deming ; editors, Patrick Lussier, Gregg Featherman ; music, Mason Daring.
Meryl Streep, Aidan Quinn, Gloria Estefan, Angela Bassett.
Keywords: Guaspari-Tzavaras, Roberta -- Drama; Violin teachers -- New York (State) -- East Harlem (New York) -- Drama; East Harlem (New York, N.Y.) -- Drama